Taxonomic revision of the Pegomya meridiana species group (Diptera: Anthomyiidae) including natural enemies of invasive Hypericum spp. (Clusiaceae) - Michelsen, Verner (Zootaxa, 2009)
The Pegomya meridiana species group is established for three Palaearctic species that supposedly all as larvae attack seed-capsules of Hypericum spp. (Clusiaceae). Pegomya meridiana (Villeneuve) and P. provecta (Villeneuve) are widespread Eurasian species, while the third species, P. canariensis Michelsen, is endemic to the western Canary Islands. Synapomorphies for the Pegomya meridiana species group are most evident in the females: A laterally compressed oviscapt with blade-shaped cerci and a unique forward displacement of spiracles VI onto tergite V. Both sexes of P. provecta and P. canariensis are further lacking abdominal spiracles VII, a character state not previously reported from Anthomyiidae. An equally novel character state is the fusion of the cercal tips seen in female P. canariensis. The taxonomic part includes illustrated descriptions, specimen records, notes on distribution and biology, and an identification key to males and females. Females of P. provecta and P. canariensis are described for the first time. Hypericum perforatum L. and H. canariense L. are known as invasive weeds outside their natural ranges, and it is pointed out that species of the P. meridiana species group might be useful in the control of alien populations of these plants through their seed-feeding larvae.